2007
DOI: 10.1007/s11102-007-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical properties of silent corticotroph adenoma and Cushing’s disease

Abstract: Proopiomelanocortin processing in corticotroph cells is known to be operated by prohormone convertase (PC) 1/3 which is activating several pro-proteins and prohormones by intracellular limited proteolysis processing. In this study, we hypothesized that PC1/3 expression differs between Cushing's disease (CD) and silent corticotroph adenoma (SCA), and investigated whether PC1/3 expression is involved in the adrenocorticotropin (ACTH) silence of SCA. We performed immunohistochemical analysis of pituitary adenoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…11 Eight per cent of patients with clinically nonfunctioning tumours had SCAs, which is again in accordance with previous reports of 10-13% SCAs among nonfunctioning adenomas. 4,13,14 The mean age at diagnosis was slightly higher than usually described in SCAs (54 years old vs 44-53) 4,11,14,15 and NFGMs (59 vs 50-55). 3,4 This could be explained by the reference centre effect, in which a low rate of post-operative complications allows clinicians to propose surgery to older patients.…”
Section: Discussionmentioning
confidence: 74%
“…11 Eight per cent of patients with clinically nonfunctioning tumours had SCAs, which is again in accordance with previous reports of 10-13% SCAs among nonfunctioning adenomas. 4,13,14 The mean age at diagnosis was slightly higher than usually described in SCAs (54 years old vs 44-53) 4,11,14,15 and NFGMs (59 vs 50-55). 3,4 This could be explained by the reference centre effect, in which a low rate of post-operative complications allows clinicians to propose surgery to older patients.…”
Section: Discussionmentioning
confidence: 74%
“…It has been shown that both PC1/3 and PC2 mRNA are expressed in ACTHsecreting pituitary tumors and NFT by conventional RT-PCR (17), and that immunoreactivities of both PC1/ 3 and PC2 are detected in the normal pituitary gland by immunohistochemical study, while immunoreactivity for PC1/3 is more abundant in ACTH-secreting pituitary tumors causing CD (15,16,18). However, PC1/3 expression in SCA by immunochemical study has shown conflicting results; negative immunoreactive PC1/3 in one case (19) versus positive immunoreactive PC1/3 in four cases (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The use of ACTH and Gal-3 immunostaining should therefore help in the diagnosis of silent ACTH adenomas. It has also been proposed that prohormone convertase 1/3 is likely to be an important etiological factor in the regulation of ACTH processing [29]. Other explanations relate to the failure of exocytosis, an increased intracellular disposal, by lysosomes, and a defective packaging into secretory granules due to inadequately developed Golgi apparatus [15].…”
Section: Discussionmentioning
confidence: 99%